2009
DOI: 10.1039/b906123a
|View full text |Cite
|
Sign up to set email alerts
|

Amino-functionalized carbon nanotubes as solid basic catalysts for the transesterification of triglycerides

Abstract: Multiwalled carbon nanotubes grafted with various amino groups show high activity and stability when used as basic catalysts for the transesterification of triglycerides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 21 publications
0
55
0
5
Order By: Relevance
“…[21,22] The most common synthetic route consists of three steps; oxidation of the surface to create carboxylic acid groups, acylation with thionyl chloride, and the anchoring of the desired molecule by amidation. [19,20] Although this technique is efficient, we found that the proximity of acidic O-containing functional groups to basic amino groups leads to weakly basic samples, showing poor catalytic activity and poor stability.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[21,22] The most common synthetic route consists of three steps; oxidation of the surface to create carboxylic acid groups, acylation with thionyl chloride, and the anchoring of the desired molecule by amidation. [19,20] Although this technique is efficient, we found that the proximity of acidic O-containing functional groups to basic amino groups leads to weakly basic samples, showing poor catalytic activity and poor stability.…”
Section: Resultsmentioning
confidence: 99%
“…[21,22] The catalysts show high stability during regeneration/recycling cycles, thus proving that the amino groups are strongly anchored to the surface of the CNTs. [22] We also proved that the basicity of the catalyst can be tuned by grafting amines with different pKa values. Herein, we studied the effect the amount of grafted amines has on the basicity of the catalyst.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, amino grafted nanotubes were produced by deprotonating CNTs with n-BuLi followed by an electrophilic substitution of bromo amino derivatives (triethylamine, ethylamine, pyrolidine) [129][130][131]. Active sites grafted by C-C coupling were significantly more active and stable for the transesterification of tributyrin than amino groups tethered by oxidation-amidation (Fig.…”
Section: Acid-base Catalyzed Reactionsmentioning
confidence: 99%